Business and marketing strategy reformulation for optik joy to develope new customer base - Firullah Pandy, Nathania; Furinto, Asnan (The Indonesian Journal of Business Administration, 2018)
Abstract — Indonesia, with total population estimated at 266.79 million, has a rapid increasing growth of consuming class. Domestic goods and service consumed by Indonesian urbanities are also increasing. 80 of 266.79million Indonesian people are wearing spectacle. Although, 30 of 80million of spectacle target market are still not reached with 1500 mid-low priced optics as competitors in optical industry. Optik JOY, which is which is the one of mid-low priced optical retailer of eyewear in Tangerang region of Indonesia, has a huge opportunity to expand in Indonesian spectacle market industry. In actual, GMV of Optik JOY mostly generated by BPJS Kesehatan Health Insurance coverage. However, regarding to some internal regulations within BPJS Kesehatan Health Insurance, Optik JOY could not expand only depend on the partnership itself. This situation challenges Optik JOY to develop the potential of new target market and out from the red ocean optical industry competition. In regards of to develop a new business and marketing strategy formulation for Optik JOY, writer do several analysis using qualitative and quantitative methods. By identifying the external forces and internal issues first, then author formulating the strategic proposal to create strategy that could leverage Optik JOY’s positioning as a mid-low priced optic and create differentiation and unique value proposition. The proposed strategy applies an adjusted segmentation, target, and positioning of Optik JOY, improved marketing strategy, and blue ocean strategy into the context of a mid-low priced optic. Keywords: business strategy, marketing strategy, optical industry